Degradation-induced capacitance: a new insight into the superior capacitive performance of polyaniline/graphene composites. Issue 11 (25th September 2017) - Zhang, Qin'e; Zhou, An'an; Wang, Jingjing; Wu, Jifeng; Bai, Hua
Abstract : Degradation of PANI induces superior performance of PANI/graphene composite electrodes with the high conductivity matrix of graphene. Abstract : Polyaniline/graphene (PANI/graphene) composites are the most investigated electrode materials for supercapacitors, owing to their high specific capacitance and excellent rate performance. However, a specific capacitance larger than the theoretical limit of the composite has been frequently reported for PANI/graphene composites, and the reason for this over-high capacitance has not been understood. In this work, after systematically investigating the evolution of the electrochemical and spectral properties of PANI/graphene, we prove that the hydroxyl- or amino-terminated oligoanilines generated from degradation of PANI possess a large specific capacitance (>1000 F g −1 ), and they significantly increase the total specific capacitance of the composite electrode. Graphene in the composite serves as a conductive matrix for electron transport between the low-conductivity hydroxyl or amino-terminated oligoanilines and the current collector. Based on the above results, we put forward a suggestion for simultaneously improving the specific capacitance and cycling stability of the PANI/graphene composites. A PANI/reduced graphene oxide composite material with a specific capacitance of 719 F g −1 at 1.4 A g −1 and 91.3% capacitance retention after 10 000 cycles is obtained.